Scanning Electron Microscopy (SEM) studies of passiflora species available in Peninsular Malaysia - Veeramohan, R.; Haron, N.W. (2014)
Micromorphological characteristics of four Passiflora species were distinguished by Scanning Electron Microscopy (SEM) studies. Stomata, trichomes, and epidermal surfaces’ structure of leaves of each species were observed using a scanning electron microscope.